2023
DOI: 10.3390/jof9030370
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the Transmembrane Transporter (swnT) Gene of the Fungus Slafractonia leguminicola Results in a Reduction of Mycotoxin Transport

Abstract: Slafractonia leguminicola infects red clover and other legumes, causing black patch disease. This pathogenic fungus also produces two mycotoxins, slaframine and swainsonine, that are toxic to livestock grazing on clover hay or pasture infested with S. leguminicola. Swainsonine toxicosis causes locoism, while slaframine causes slobbers syndrome. The mechanism of toxin secretion by S. leguminicola is poorly understood. The aim of this research was to investigate the role of a putative transmembrane transporter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Previous work showed that silencing of swnT had a significant effect on S. leguminicola growth and pathogenicity and effected secretion of both swainsonine and slaframine [38]. This differed significantly from knockouts of swnT in Metarhizium, which caused no change in growth of the fungus and no change in secretion.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Previous work showed that silencing of swnT had a significant effect on S. leguminicola growth and pathogenicity and effected secretion of both swainsonine and slaframine [38]. This differed significantly from knockouts of swnT in Metarhizium, which caused no change in growth of the fungus and no change in secretion.…”
Section: Introductionmentioning
confidence: 87%
“…Standards and sample extracts were analyzed by HPLC-HRMS using the following instrumentation [38]. A Q-Exactive quadrupole/orbitrap high-resolution mass spectrometer (Thermo Scientific) equipped with a heated electrospray ion source (HEIS) and coupled to an Ultimate 3000 HPLC (Thermo Scientific) was used for analyses.…”
Section: Hplc-hrms Analysismentioning
confidence: 99%
See 3 more Smart Citations